A simple model of squatters - Remolona, Eli M. (The Philippine Review of Business and Economics, 1984)
The object of the model is to determine the number of squatters in a city. In the model, households with incomes below a certain threshold level of income choose to squat and households with income above that threshold choose not to squat. This threshold depends on the amount of land available to each squatter household, which itself depends on the number of households choosing to be squatters. The equilibrium established consists of values for the threshold and the amount of land per squatter household that are both consistent with utility maximizing choices, given such factors as the rate of eviction and the distribution of income. An increase in the rate of eviction will reduce the equilibrium number of squatters in a city even if the total amount of squatter land remains fixed. Fewer household choose to squat because of this higher risk of eviction. A numerical example is presented to show how plausible the model is.